Injectable ROS-scavenging hydrogel with MSCs promoted the regeneration of damaged skeletal muscle. (July 2021) - Shan, Huajian; Gao, Xiang; Zhang, Mingchao; Huang, Man; Fang, Xiyao; Chen, Hao; Tian, Bo; Wang, Chao; Zhou, Chenyu; Bai, Jinyu; Zhou, Xiaozhong
Skeletal muscle injury is a common disease accompanied by inflammation, and its treatment still faces many challenges. The local inflammatory microenvironment can be modulated by a novel ROS-scavenging hydrogel (Gel) we constructed. And MSCs could differentiate into myoblasts and contribute to muscle tissue homeostasis and regeneration. Here, Gel loaded with mesenchymal stem cells (MSCs) (Gel@MSCs) was developed for repairing the injured skeletal muscle. Results showed that the Gel improved the survivability and enhanced the proliferation of MSCs (≈two-fold), and the Gel@MSCs inhibited the local inflammatory responses as it promoted polarization of M2 macrophages (increased from 5% to 17%), the mediator of the production of anti-inflammatory factors. Western blotting and qPCR revealed the Gel promoted the expression of proteins (≈two-fold) and genes (≈two to six-fold) related to myogenesis in MSCs. Histological assessment indicated that the Gel or MSCs promoted regeneration of skeletal muscle, and the efficacy was more significant at Gel@MSCs than MSCs alone. Finally, behavioral experiments confirmed that Gel@MSCs improved the motor function of injured mice. In short, the Gel@MSCs system we constructed presented a positive effect on reducing skeletal muscle damage and promoted skeletal muscle regeneration, which might be a novel treatment for such injuries.